Ferroptosis plays a novel role in nonalcoholic steatohepatitis pathogenesis - Xiong, Fei; Zhou, Qiao; Huang, Xiaobo; Cao, Peng; Wang, Yi (Frontiers in Pharmacology, 2022)
Ferroptosis relies on iron, and ferroptotic cell death is triggered when the balance of the oxidation‒reduction system is disrupted by excessive lipid peroxide accumulation. A close relationship between ferroptosis and nonalcoholic steatohepatitis (NASH) is formed by phospholipid peroxidation substrates, bioactive iron, and reactive oxygen species (ROS) neutralization systems. Further study into ferroptosis during NASH development might reveal NASH pathogenesis and drug targets, as indicated by recent research. Our review explores NASH pathogenesis due to ferroptotic mechanisms. Moreover, it explores mitochondrial dysfunction in ferroptosis. Finally, potential pharmacological therapies directed to ferroptosis in NASH are discussed.